COULOMB SYSTEMS WITH CALOGERO INTERACTION - Hakobyan, T.S.; Nersessian, A.P. (Proceedings of the YSU A: Physical and Mathematical Sciences, 2016)
We describe the integrals of motion of the high-dimensional Coulomb system with and without the Stark term, perturbed by the Calogero interaction.